Propagação vegetativa de Bambusa vulgaris - Braga, Rafael Malfitano (2017)
Bamboo is an important source of raw material of multiple uses. The development of simple techniques for its propagation is a practical way to enable its implementation in ownership of low technology. The present work had the objective of evaluating artisanal propagation methods for Bambusa vulgaris. Two types of propagules were tested, with buds budded or not, and three relative positions to the removal of vegetative material on the culm. The best propagule was with only one node, extracted from the lower thirds of the stem, presenting 72% of rooting. This result demonstrates its potential for seedling production of this species under low tech.